1995
DOI: 10.1007/bf00186788
|View full text |Cite
|
Sign up to set email alerts
|

Cell migration from the transplanted olfactory placode in Xenopus

Abstract: The eye vesicle of Xenopus borealis has been replaced with the transplanted olfactory primordium from Xenopus laevis in an attempt to determine whether cells from the transplant could migrate along the regrowing olfactory nerve and become incorporated into the CNS of the host. The use of X. laevis and X. borealis pairs allowed us to distinguish the cells of the host from those of the donor at the cellular level by means of the characteristic fluorescent nuclear spots (Q bands) of X. borealis. Transplantation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…The generation of neurons from our grafts is consistent with previous studies on frogs in which ectopic nasal placodes were grafted in locations close to the brain (Byrd and Burd, 1993;Koo and Graziadei, 1995;Stout and Graziadei, 1980). However, in these studies, not only did olfactory nerves form, but in the case of the midline grafts the ectopic nerve made the correct connection to the olfactory bulb (Byrd and Burd, 1993;Stout and Graziadei, 1980).…”
Section: Autonomous Differentiation Of the Nasal Pit Epithelium Is Susupporting
confidence: 90%
See 1 more Smart Citation
“…The generation of neurons from our grafts is consistent with previous studies on frogs in which ectopic nasal placodes were grafted in locations close to the brain (Byrd and Burd, 1993;Koo and Graziadei, 1995;Stout and Graziadei, 1980). However, in these studies, not only did olfactory nerves form, but in the case of the midline grafts the ectopic nerve made the correct connection to the olfactory bulb (Byrd and Burd, 1993;Stout and Graziadei, 1980).…”
Section: Autonomous Differentiation Of the Nasal Pit Epithelium Is Susupporting
confidence: 90%
“…This could mean that the mesenchyme lacks the signals to maintain olfactory epithelial gene expression, or that the maxillary mesenchyme suppresses the site-specific gene expression in the nasal epithelium. Nonetheless, even in the absence of stereotypic gene expression, the nasal pit can form nasal passages and neurons in other areas of the embryonic face.The generation of neurons from our grafts is consistent with previous studies on frogs in which ectopic nasal placodes were grafted in locations close to the brain (Byrd and Burd, 1993;Koo and Graziadei, 1995;Stout and Graziadei, 1980). However, in these studies, not only did olfactory nerves form, but in the case of the midline grafts the ectopic nerve made the correct connection to the olfactory bulb (Byrd and Burd, 1993;Stout and Graziadei, 1980).…”
supporting
confidence: 90%
“…Finally, it is of interest to note an additional finding in the present study that the axons of growing SST‐ir olfactory nerve fibers could extend along the spinal nerve from the olfactory placode transplant to the spinal cord. There are reports that olfactory axons were observed to grow from the transplanted olfactory placode in the sites of removed optic vesicle and that the trigeminal placode reached the diencephalon and the hindbrain, respectively (Koo & Graziadei, 1995; Gao et al ., 2000). In our study, the olfactory axons were found to grow in the peripheral nerve tract and their pathway extended up to the spinal code.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the olfactory fibers that terminate ectopically produce characteristic glomerular formations similar to the classic structures of the olfactory bulb (Stout and Graziadei 1980;Magrassi and Graziadei 1985). It is also of considerable interest that a stream of placodal cells migrates from the transplanted olfactory placode and then mingles in the host's CNS with other neuronal populations to aid in the formation of characteristic hyperplastic regions (Koo and Graziadei 1995). These regions of hyperplasy/hypertrophy have been previously observed by other authors, as well as by us, as a result of the interaction of the olfactory placode with the CNS (Bell 1906(Bell , 1907Burr 1924Burr , 1930.…”
Section: Introductionmentioning
confidence: 99%